Investigational Security Structural Design Using Client and Server Ambitious Protocols for WMN - Selvakani Kandeeban; N Suresh Kumar (Institute of Advanced Engineering and Science, 2015)
Wireless mesh network plays an vital role in our day to day life, Networks are mainly used to deliver voice, video and data but using WMN’s we can communicate in outdoor environments without wired. A wireless mesh can deliver network capacity, reliability and security along with the flexibility. Nowadays the WMN’s are used by municipalities, public safety agencies, port authorities, and industrial organizations to connect to their workers and constituents. However, many technical issues still exist in this field. In order to provide a better understanding of the research challenges of WMNs, In this paper we propose MobiSEC, a complete security architecture protocols and algorithms for WMNs that provides both access control for mesh users and routers as well as a key distribution schemes that supports layer-2 encryption to ensure security and data confidentiality of all communications that occur in the WMN.